WHEN CULTURE RECOMPOSE THE PEOPLE: bases of anti-colonial struggle in the 1973-1989 military dictatorship period in Gulu Mapu - Huircapan, Sergio Caniuqueo (Universidade de Brasília, 2018)
Abstract: This article attempts to address two phenomena that develop during the period of military dictatorship in Gulumapu, the first is the reconfiguration of Chilean colonialism, and two, as diverse cultural expressions are transformed into a political theoretical framework, which over time form the basis for a cultural anticolonialism and the construction of the notion of people and nation, and that transversalize the action of groups of left and right within the Mapuche society. Paradoxically these phenomena have been little addressed and there is a lack of knowledge of their contributions. We tried to show how history, culture and language were becoming the matrix to think about the demands and demands to assume the condition of people and with rights that are theirs. Key words: Military dictatorship, anti-colonial struggle, Mapuche, rights